The godmother : a crime novel - Cayre, Hannelore, 1963- (ECW, 2019)
"Meet Patience Portefeux, fifty-three, an underpaid FrancoArab judicial interpreter for the Ministry of Justice who specialises in telephone tapping. Widowed after the sudden death of her husband, Patience is now wedged between university fees for her two grown-up daughters and nursing home costs for her ageing mother. Shes laboured for twenty-five years to keep everyone's heads above water. Happening upon an especially revealing set of police wiretaps ahead of all other authorities, Patience makes a life-altering decision that sees her intervening in and infiltrating the machinations of a massive drug deal. She thus embarks on an entirely new career path: Patience becomes the Godmother. This is not life in the French idyll of postcards and stock photos. With a gallery of traffickers, dealers, police officers and politicians who are more real than life itself, a sharp and amusing gaze on everyday survival in contemporary France, and an unforgettable woman at its centre, Hannelore Cayres bestselling novel shines a torchlight on a European criminal underground that has rarely been seen."--